Gerakan Penolakan Koalisi Masyarakat Sipil untuk Reformasi Sektor Keamanan terhadap Revisi Undang-Undang TNI 2025 - Aldira Dwi Yunianto Yunianto; Valina Singka Subekti (MIMBAR : Jurnal Sosial dan Pembangunan, 2026)
Indonesia faces democratic regression marked by the revision of the Indonesian Military Law (TNI Law) enacted on 20 March 2025, widely perceived as a threat to civilian supremacy and a potential revival of military dual-function practices. While prior studies have examined democratic decline and military reform in Indonesia separately, none has specifically analyzed how civil society constructs and sustains collective resistance against this revision. This study addresses that gap by examining the Coalition for Civil Society for Security Sector Reform, applying (McAdam, Tarrow, and Tilly, 2004)) contentious politics framework through a qualitative case study involving in-depth interviews and document analysis. The coalition sustains resistance through four interrelated elements: opportunities and threats, mobilizing structures, framing processes, and repertoires of contention. Although the law is enacted, the coalition maintains contention through judicial review and post-enactment advocacy. The findings offer practical insights for strengthening civilian oversight, informing civil-military relations policy, and supporting institutional safeguards against military expansion into civilian governance in Indonesia and comparable democratizing contexts.